The seismic and rock-physics evidences of the different migration efficiency between different types of gas chimneys. (January 2023) - Deng, Wei; Zenggui, Kuang; Jinqiang, Liang; Pin, Yan; Lu, Jingan; Meng, Miaomiao
Abstract: Gas chimney and the associated fluid migrations are important for understanding the accumulation of gas hydrates worldwide. Two adjacent gas chimneys (GC1 and GC2) both originate from the Songnan low uplift in the Qiongdongnan Basin, and many fluid seepage pathways with various intensities were identified inside the shallow massive transport deposits (MTDs) on the top of the gas chimneys. Seismic attributes indicate that GC1 covers wide areas, and the seepage pathways are sporadically and irregularly distributed over GC1. GC2 is another type of gas chimney which is associated with a fault that communicated deep uplift to the MTDs, and more seepage pathways with larger diameters above GC2 were present along the fault. From the X-CT images of pressure cores with fracture-filling hydrates and elastic-electrical anisotropy analysis of well logs, hydrates are mainly present in vertical fractures in the seepage pathways above GC1, while many horizontal fractures in those pathways near the fault above GC2 were identified. Because the gas pressure needed to induce vertical fractures is smaller than horizontal fractures, the minimal heights of the gas column in GC1 and GC2 were at least 90.9m and 163.26m, respectively, based on the fracturing criterion. It also indicates that GC2 owns a higher migration efficiency. Meanwhile, rock physic inversion reveals that high-intensity seepages above GC2 create more fracture-filling hydrates, and increase the primary porosity of the sediments as well. This study reveals these new and quantitative core-well logging-seismic evidences of two types of chimneys with completely different fluid migration mechanisms, offering insights into studying fluid migration related to gas chimneys worldwide. Highlights: The gas chimney with a fault is a high-efficiency supply pathway. The distribution of seepages and the fracture dips are related to the migration efficiency. Adequate gas source produces more fracture porosities in shallow sediments.